Effect of the grid geometry on the convective heat transfer of impinging jets. (January 2017) - Cafiero, Gioacchino; Castrillo, Giusy; Greco, Carlo Salvatore; Astarita, Tommaso
Highlights: Experimental investigation of an impinging jet with a multiclass of grids. Effects investigated: grid thickness ratio, initial pattern, number of iterations. A larger thickness ratio leads to a higher heat transfer at short distances. The secondary iterations play a key-role in the heat transfer enhancement process. The circular pattern provides a more uniform convective heat transfer rate. Abstract: Passive methods are recognized as one of the most efficient means to achieve high heat and mass transfer in impinging jets. In a recent study, Cafiero et al. (2014) demonstrated the effectiveness of square fractal grids (SFGs, obtained repeating the same square pattern at increasingly smaller scales) in terms of heat transfer enhancement when locating the grid in correspondence of the nozzle exit section. Indeed, the capability of producing turbulence at multiple scales and the possibility of tuning the peak in the turbulence intensity profile as a function of the grid geometric parameters are both extremely appealing for heat transfer enhancement purposes. In this study, the effect of the grid geometry on the convective heat transfer rate of impinging jets is assessed and discussed. Three main effects are taken into account: the grid thickness ratio (obtained by varying the thickness of the first iteration of the SFG), the effect of the secondary grid iterations and the choice of the initial pattern. It is demonstrated how a larger thickness ratio, which in the present case corresponds to an anticipated location of the peak in the turbulence intensity profile, is beneficial to get a spotted high convective heat transfer rate at short nozzle to plate distances. Either the use of a single square grid, or the choice of a different initial pattern (for example a circular fractal grid) is instead indicated when it is desirable a uniform distribution of the convective heat transfer rate.